Birth weight and anthropometric measurements of twins - Shayesteh Jahanfar (Taylor & Francis Group, 2018)
Background: Genetic and environmental influences on anthropometric measures can be investigated by comparing dizygotic (DZ) versus monozygotic (MZ) twins. Investigating cohorts living in different geographical areas across the globe can identify the variation in heritability versus environment. Aims: (1) To investigate the association between birth weight and anthropometric measurements during adulthood; (2) to study the genetic and environmental influences on body measures including birth weight, weight and height among twins; and (3) to assess the variation in heritability versus environment among two cohorts of twins who lived in different geographical areas. Subjects and methods: Twins were collected from two twin registers. Data on birth weight, adult weight and height in 430 MZ and 170 DZ twins living in two geographically distinct parts of the world were collected. A genetic analysis was performed using MX software. Results: Birth weight was associated with weight, height and BMI. Both MZ and DZ twins with low birth weight had shorter height during their adult life (p = 0.001), but only MZ twins with lower birth weight were lighter at adulthood (p = 0.001). Intra-pair differences in birth weight were not associated with differences in adult height (p = 0.366) or weight (p = 0.796). Additive genetic effects accounted for 53% of the variance in weight, 43% in height and 55% in birth weight. The remaining variance was attributed to unique environmental effects (15% for weight, 13% for height and 45% for birth weight and only 16% for BMI). Variability was found to be different in the two cohorts. The best fitting model for birth weight and BMI was additive genetic and non-shared environment and for weight and height was additive genetic, non-shared environment (plus common Environment). Conclusions: Data suggests that the association between weight at birth and anthropometric measures in later life is influenced by both genetic and environmental factors. Living in different environments can potentially relate to variation found in the environment.